2010
DOI: 10.1158/1535-7163.mct-09-1147
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GRIM-19 in Cancer Cells Suppresses STAT3-Mediated Signal Transduction and Cancer Growth

Abstract: Constitutive activation of signal transducer and activator of transcription 3 (STAT3) is common in many human and murine cancer cells, and its activation leads to cellular transformation. STAT3 pathway inhibitors have been reported to suppress cancer growth. To investigate the antitumor effects of inhibiting the STAT3-mediated signaling cascade in the cancer microenvironment, using a molecular-targeting approach, we focused on the gene associated with retinoid-IFN-induced mortality 19 (GRIM-19). GRIM-19 has be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
(53 reference statements)
2
25
0
Order By: Relevance
“…GRIM-19 suppressed not only tumor growth but also neoangiogenesis (19). Consistent with its tumor-suppressive characteristics, we and others have documented a loss of GRIM-19 expression in a number of primary human cancers of the kidney, colon, brain, prostate, lung, and cervix (19,(44)(45)(46)(47)(48)(49)(50)(51). More recently, we have identified functionally inactivating somatic mutations in GRIM-19 in primary human oral SCCs (16).…”
Section: Discussionsupporting
confidence: 75%
“…GRIM-19 suppressed not only tumor growth but also neoangiogenesis (19). Consistent with its tumor-suppressive characteristics, we and others have documented a loss of GRIM-19 expression in a number of primary human cancers of the kidney, colon, brain, prostate, lung, and cervix (19,(44)(45)(46)(47)(48)(49)(50)(51). More recently, we have identified functionally inactivating somatic mutations in GRIM-19 in primary human oral SCCs (16).…”
Section: Discussionsupporting
confidence: 75%
“…GRIM-19 is selective for STAT3 and is not known to bind the other STAT family members. By binding to nuclear STAT3, GRIM-19 (Kalakonda et al, 2007;Okamoto et al, 2010;Wang et al, 2011). Moreover, there is evidence that the mitochondrial localization of GRIM-19 in and of itself enhances cytokine-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, R9-fusion proteins could be efficiently transduced into all tested cell types in culture, including hematopoietic cells ( Fig. 2A) [27][28][29]. Tunnemann et al also demonstrated similar (cell transduction/cell viability) results with an R9-peptide [30].…”
Section: Protein-transduction Domain (Ptd)/cell-penetrating Peptide (supporting
confidence: 81%